Updated landslide inventory of the area between the Furiano and Rosmarino creeks (Sicily, Italy). Issue 5 (19th October 2016) - Raspini, Federico; Ciampalini, Andrea; Bianchini, Silvia; Bardi, Federica; Di Traglia, Federico; Basile, Giuseppe; Moretti, Sandro
ABSTRACT: A 1:10, 000 scale landslide inventory map has been prepared for the area between the Furiano and Rosmarino creeks, in the Nebrodi Mountains (north-eastern Sicily, Italy), a territory highly prone to slope failures, due to the local geological and geomorphological settings and intense rainfall. The landslide inventory database included within the Hydrogeological Setting Plan of the Sicily Region has been used as a starting point for this work. The updated inventory map has been compiled through a combination of conventional approaches (i.e. aerial photo-interpretation and field surveys) and new remote sensing techniques (ground deformation measurements obtained by interferometric analysis of satellite Synthetic Aperture Radar images). The new landslide inventory consists of 566 events, classified according to their typology and state of activity.